Oxidized LDL Levels Are Increased in HIV Infection and May Drive Monocyte Activation. (1st June 2015) - Zidar, David A.; Juchnowski, Steven; Ferrari, Brian; Clagett, Brian; Pilch-Cooper, Heather A.; Rose, Shawn; Rodriguez, Benigno; McComsey, Grace A.; Sieg, Scott F.; Mehta, Nehal N.; Lederman, Michael M.; Funderburg, Nicholas T.
Abstract : Background: HIV infection is associated with increased cardiovascular risk, and this risk correlates with markers of monocyte activation. We have shown that HIV is associated with a prothrombotic monocyte phenotype, which can be partially mitigated by statin therapy. We therefore explored the relationship between oxidized low-density lipoprotein (oxLDL) particles and monocyte activation. Methods: We performed phenotypic analysis of monocytes using flow cytometry on fresh whole blood in 54 patients with HIV and 24 controls without HIV. Plasma levels of oxLDL, soluble CD14, IL-6, and soluble CD163 were measured by enzyme-linked immunosorbent assay. In vitro experiments were performed using flow cytometry. Results: Plasma levels of oxLDL were significantly increased in HIV infection compared with controls (60.1 units vs. 32.1 units, P < 0.001). Monocyte expression of the oxLDL receptors, CD36 and Toll-like receptor 4, was also increased in HIV. OxLDL levels correlated with markers of monocyte activation, including soluble CD14, tissue factor expression on inflammatory monocytes, and CD36. In vitro stimulation with oxLDL, but not to low-density lipoprotein, resulted in expansion of inflammatory monocytes and increased monocyte expression of tissue factor, recapitulating the monocyte profile we find in HIV disease. Conclusions: OxLDL may contribute to monocyte activation, and further study in the context of HIV disease is warranted.